Chimica farmaceutica: farmaci sistemici: Lezioni del prof. Ettore Novellino Pharmaceutical chemistry: Lectures by prof. Ettore Novellino - Ilario Sepe (Phármakon, 2017)
For thousands of years, pharmacological knowledge coming from natural remedies, has been handed down from generation to generation, without any awareness of the ways in which preparations are made to face diseases. The advent of pharmaceutical chemistry and of the modern drug industry turned that lack of awareness into a scientific knowledge that changed the destiny of the human race. The twenty-eight chapters of this book, are taken from the lectures held by Professor Ettore Novellino every year in his course "Pharmaceutical Chemistry and Toxicology 2". The first chapters address the basic notions of drugs, homeostasis, pharmacopoeia, and receptor; then, the different pharmaceutical classes are introduced by analyzing their pharmacological and chemical aspects. In particular, the structural study of the interaction between drugs and receptors or biological enzymes gives the fundamentals to connect the chemical and stereochemical properties of a compound family, with the biological activity, a correlation better known as Quantitative Structure-Activity Relationship (QSAR). Several examples of the synthesis of some of the most historically renown drugs, provided at the end of each chapter, integrate the book.